Burning savanna for avian species richness and functional diversity. Issue 4 (26th March 2020) - Docherty, Teegan D. S.; Hethcoat, Matthew G.; MacTavish, Lynne M.; MacTavish, Dougal; Dell, Stephen; Stephens, Philip A.; Willis, Stephen G.
Abstract: Prescribed fire is used throughout fire‐prone landscapes to conserve biodiversity. Current best practice in managing savanna systems advocates methods based on the assumption that increased fire‐mediated landscape heterogeneity (pyrodiversity) will promote biodiversity. However, considerable knowledge gaps remain in our understanding of how savanna wildlife responds to the composition and configuration of pyrodiverse landscapes. The effects of pyrodiversity on functional diversity have rarely been quantified and assessing this relationship at a landscape scale that is commensurate with fire management is important for understanding mechanisms underlying ecosystem resilience. Here, we assess the impact of spatiotemporal variation in a long‐term fire regime on avian diversity in North West Province, South Africa. We examined the relationship between (1) species richness, (2) three indices of functional diversity (i.e., functional richness, functional evenness, and functional dispersion) and four measures of pyrodiversity, the spatial extents of fire age classes, and habitat type at the landscape scale. We then used null models to assess differences between observed and expected functional diversity. We found that the proportion of newly burned (<1‐yr post‐fire), old, unburned (≥10 yr post‐fire), and woodland habitat on the landscape predicted species and functional richness. Species richness also increased with the degree of edge contrast between patches of varying fire age, while functional dispersion increased with the degree of patch shape complexity. Lower than expected levels of functional richness suggest that habitat filtering is occurring, resulting in functional redundancy across our study sites. We demonstrate that evaluating functional diversity and redundancy is an important component of conservation planning as they may contribute to previously reported fire resilience. Our findings suggest that it is the type and configuration, rather than the diversity, of fire patches on the landscape that promote avian diversity and conserve ecological functions. A management approach is needed that includes significant coverage of adjacent newly burned and older, unburned savanna habitat; the latter, in particular, is inadequately represented under current burning practices.